NEW TECHNOLOGIES AND BIOMATERIALS FOR THE GTR AND GINGIVAL PLASTIC SURGERY. REVIEW - Irina-Georgeta Sufaru; Ionut Luchian; Maria-Alexandra Martu; George-Alexandru Maftei; Andrei Nicolau; Oana Butnaru; Silvia Martu; Sorina-Mihaela Solomon (Romanian Dental Association for Education, 2021)
Periodontal treatment of tissue defects which comprises guided tissue regeneration and mucosal plastic surgery still remains nowadays a challenge in the dental office due to the lack of absolute predictability. New treatment techniques and biomaterials have emerged in order to counteract the different risks generated by the periodontal surgical methods. 3D and 4D printing technologies offer new possibilities in terms of patient-tailored materials, with lower complications and trauma and with the promise of a more accurate treatment plan and success.